Fostering The Future: The Z-Generation In Discovering The Meaning Of Life And Optimism - Hamdaniati, Aliyatil (Academic Journal of Psychology and Counseling, 2024)
The study of meaning, in philosophy and psychology, is important to reveal the influences toward individual well-being, especially optimism. This study examined the influences of various factors, such as social media, family environment, education, and personal experiences on Z-generation’s perception of the meaning of life and their levels of optimism. Age, sex type, and spirituality are influential factors for searching for meaning in life, found based on the journal article review. The Age influences a person’s search for life’s meaning and their optimism. Sex type also plays an important role; men tend to discover meaning in life through family roles and social relationships, while women tend to discover meaning through achievement and independence. Spirituality, such as religious practices and spiritual beliefs, offers a framework to discover the meaning of life and remain optimistic, especially through the social support of the spiritual community.